MOFs-based adsorbents for the removal of tetracycline from water and food samples - Arezou Khezerlou; Milad Tavassoli; Reza Abedi-Firoozjah; Mahmood Alizadeh Sani; Ali Ehsani; Rajender S. Varma (Scientific Reports)
Abstract Tetracyclines (TCs) are widely employed for the prevention and treatment of diseases in animals besides being deployed to promote animal growth and weight gain. Such practices result in trace amounts of TCs occurrence in water and foodstuffs of animal origin, including eggs and milk, thus posing severe health risks to humans. To ensure the food and water safety and to avoid exposure to humans, the removal of TC residues from food and water has recently garnered a considerable attention. Metal-organic frameworks (MOFs), endowed with unique structural and surface properties with high affinity toward TCs, are recognized as excellent absorbents for removal of TCs from food and water samples. Herein, the utilization of MOFs in the adsorption of TC from food and water samples is deliberated including the underlying mechanisms and various factors that affect the adsorption and degradation of TCs. The strategy may be extendible to other pollutants as well.